The Intersection of Law and Science: Advancing Criminal Investigations - Naik, Abdul Rouf; D, Sankar (PRAWO i WIĘŹ, 2025)
The integration of digital evidence, psychological profiling, forensic science, and sophisticated analytical methods in criminal investigations and judicial proceedings is examined in this study. The significance of artificial intelligence and data analytics in case evaluation is also discussed, as is the function of forensic methods, such as DNA analysis, fingerprint identification, ballistics, and others, in establishing factual evidence. To maintain law and order in our society, this study will examine how scientific and contemporary technologies are used in criminal investigations. The issues with investigations, modern sciences, and the fundamentals of forensics in India are also covered.